Performance analysis of football in the blogosphere: Measuring the high press - James, N.; Gethin, R.; Vuckovic, G. (Journal of Human Sport & Exercise, 2017)
Quantitative methods to determine which performance indicators are key to success within football have largely centred on on-the-ball activity. Thus the majority of empirical research has been developed on goal data (e.g. Bate, 1988, Hughes and Franks, 2005), shot data (e.g. Lago-Ballesteros & Lago, 2010), possession (e.g. Lago, 2009, Lago & Delall, 2010) and passing (e.g. Szwarc, 2004, Oberstone, 2009) to discriminate top, middle and bottom teams. As scoring is the ultimate objective in football, and for this to occur a team has to attempt a shot, analysis of shooting tendencies has been used as a measure of a team`s ability. Recent work has attempted to use shots as a way of describing `dominance` in individual matches. The premise being that if one team has increased their shot production, whilst limiting their opposition`s attempts at goal, then this is a strong indicator of `dominance` in that particular match, irrespective of other elements of play such a possession or passes. Total Shots Ratio (TSR) is one such metric which attempts to measure a team`s dominance over their opposition in a given match simply by using shot data of both teams and creating a score based upon the following equation; TSR = Total shots for/(Total shots for + total shots against). The equation generates a team score of between 0.0 and 1.0, with any team achieving a score over 0.5 being seen to have dominance over the opposition. Similarly, Shots on Target Ratio (SoTR) works in exactly the same way, but only using shots that were deemed to be on target. The rationale being that such shots are a better indicator of quality of chance created. Furthermore, Shot Dominance (ShotDom) explains dominance in a game by developing a ratio measure between the two competing teams in their shots created; that is if Team A has 10 shots and Team B has 5 shots, then Team A has a ShotDom score of 2.0, whilst Team B has a score 0.5. Such metrics are popular in on-line blogging communities, but as yet have received little academic investigation. The following investigation will use Opta data from the 2014-15 English Premier League season, collected from the 442Statszone website in an attempt to (a) assess the frequency that the winning team exhibits a superior score in each of the shot metrics, TSR, SoTR and ShotDom (b) via developing team average scores for each of these statistics, correlate against final league standing and (c) compare these statistics against traditional statistics possession and pass completion rate. Results can potentially provide useful information regarding the robustness of such metrics, whilst providing important summary information regarding the effectiveness of a team`s tactics in a particular match.